IMPLEMENTASI E-GOVERNMENT HUMAS PEMERINTAH PROPINSI RIAU DALAM KOMUNIKASI BENCANA - Adhianty Nurjanah, Aswad Ishak, Sakir (Jurnal Ilmu Komunikasi, 2019)
In disaster communication, the government needs to carry out communication activities appropriately. The implementation of E-government is a must to do. The use of internet-based communication media by the government, in general, is still limited. This article wants to see how the application of internet-based communication media in communicating smog disasters in Riau Province. The theoretical concept used is e-government, government public relations, and disaster communication. These three concepts are considered in accordance with the problems at hand. Data obtained through interviews, focus group discussion. The findings obtained indicate that in the smog disaster communication the Riau Provincial Government has been implementing e-government.